Publication trends in telesupervision: A content analysis study. Issue 1 (2nd January 2019) - Inman, Arpana G.; Bashian, Hannah; Pendse, Asmita C.; Luu, Linh P.
ABSTRACT: Thirty-five empirical studies from 25 peer-reviewed journals and one book chapter were analyzed through a content analysis for trends in publication, methodological, and research foci in telesupervision between 1990 and 2016. The most significant increase in publications occurred in the past decade. Methodological trends revealed that video-conferencing, webcam, and cybersupervision were frequent terminologies used to describe telesupervision. Studies were focused on supervisee experiences, used an individual supervision method, a videoconferencing medium of supervision delivery, and a qualitative methodology with both male-female samples. Studies examined three topics: effectiveness of telesupervision, counselor development, and supervisory relationship. Implications and future research directions are discussed.